2014
DOI: 10.1039/c4ob00552j
|View full text |Cite
|
Sign up to set email alerts
|

Chiral derivatives of 1,2-benzenedisulfonimide as efficient Brønsted acid catalysts in the Strecker reaction

Abstract: Two chiral derivatives of 1,2-benzenedisulfonimide, namely 4-methyl-3,6-bis(o-tolyl)-1,2-benzenedisulfonimide and 4,5-dimethyl-3,6-bis(o-tolyl)-1,2-benzenedisulfonimide, have been easily synthesized in good overall yields (respectively 34% and 41%) by means of an eleven-step synthetic protocol from commercially available 2-methyl-6-nitroaniline or 2,3-dimethyl-6-nitroaniline. 4,5-Dimethyl-3,6-bis(1-naphthyl)-1,2-benzenedisulfonimide was also synthesized, but the overall yield from 2,3-dimethyl-6-nitroaniline w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…The poor reactivity observed under photochemical conditions confirmed that the reaction occurs preferentially under thermal/chemical activation. In another recent article, Barbero and Dughera have utilized arenediazonium o‐ benzenedisulfonimides as the coupling partners for gold‐catalyzed Heck coupling reactions (Scheme ) …”
Section: Oxidant‐free Approaches For Homogeneous Au‐catalyzed Cross‐c...mentioning
confidence: 99%
“…The poor reactivity observed under photochemical conditions confirmed that the reaction occurs preferentially under thermal/chemical activation. In another recent article, Barbero and Dughera have utilized arenediazonium o‐ benzenedisulfonimides as the coupling partners for gold‐catalyzed Heck coupling reactions (Scheme ) …”
Section: Oxidant‐free Approaches For Homogeneous Au‐catalyzed Cross‐c...mentioning
confidence: 99%
“…Dughera and co-workers synthesized a sulfonimide derivative with an atropisomeric p-terphenyl structure (Scheme 80). 87 The C 2 chiral compound catalyzed the three-component Strecker reaction of aromatic aldehydes or methylketones, aniline derivatives, and (CH 3 ) 3 SiCN to give the aminonitrile products in moderate yield and in up to 97% ee.…”
Section: Introductionmentioning
confidence: 99%
“…In other cases, the use of solvents as dichloromethane, toluene or chloroform, and temperatures higher than rt was required. Similarly, soluble catalysts, such as o- benzene­disulfonimide, and sulfonic acid based nanoreactors have also been employed in larger catalyst loadings. InPF-110, even without any solvent, also outperforms previously reported MOFs tested in the same reaction, as shown in SI Table 5.2.…”
mentioning
confidence: 99%